The influence of Stimpo and Regoplant for the growth, photosynthetic pigments and protein content in seedlings of rape on technogenically disturbed substrates - Макогоненко, С. Ю.; Баранов, В. І.; Карпінець, Л. І. (Problems of Environmental Biotechnology, 2018)
Effects of biotechnological drugs – growth regulators (GR) Stimpo and Regoplant (“Agrobiotech”, Ukraine) on morphometric growth parameters, the content of photosynthetic pigments and protein in the rape (Brassica napus L.) seedlings grown on a coal rocky dumps substrates of the Chervonograd Сentral Enrichment Factory were studied. The optimal concentrations for Stimpo and Regoplant – 0.1 and 0.25 ml/l, and the optimum time of seed soaking (1 hour) were revealed. Seed treatment with the regulators improved seedlings morphometric parameters both on the garden soil and on the rock dumps substrates of the coal mines. When treated with growth regulators, the chlorophyll content a was increased in seedlings on all substrates, as invariants treated with GC, and to a greater extent under the action of Regoplant and Stippo, when compared with variants without processing. Seedlings treatment with GR leads to increment of their light deficiency tolerance at all substrates, except the variants with the GA and Stimpo on the black damp substrate. The content of the protein was lower in seedlings on the substrate of the dump than on the garden soil, both with and without the processing of GR. When comparing the protein content of sprouts with growth on substrates, processing of GR increased its content. Thus, application of growth regulators Stimpo and Regoplant seems a promising tool for the stimulation of the rape growth and metabolism both on an ordinary soil and technogenically disturbed substrates.